Developmental effects of embryonic exposure to a water-soluble fraction of crude oil on early life stages of capelin (Mallotus villosus) - Granlund, Adina Cassandra (UiT Norges arktiske universitet, 2020)
The rise in offshore oil and gas operations, maritime shipping and tourism in northern latitudes enhance the risk of petroleum pollution and anthropogenic impacts of oil-related compounds on sub-Arctic and Arctic organisms. In particular, there is a need to investigate the potential adverse effects of petroleum to the early life stages of capelin ( Mallotus villosus ), an important forage and commercial fish species that spawn along the coast of Northern Norway. In this study, newly fertilized capelin embryos were exposed to five concentrations (control, low, medium, high and extra high) of a water-soluble fraction (WSF) of crude oil using oiled gravel columns loaded with either clean gravel (control) or gravel loaded with between 0.19 and 6 g oil/kg gravel (low to extra high groups). Embryos were exposed to decreasing crude oil WSF until hatch (25 days post fertilization) and larvae were followed in clean water until 58 days post fertilization. The initial aqueous total polycyclic aromatic hydrocarbon (PAHs) levels (sum of 44 PAHs) were ranging from 0.072 to 19.25 μg/L in the five treatment groups and decreased exponentially over time. None of the measured endpoints regarding embryo development and mortality, larval length, growth rate, cardiac activity, arrhythmia, and larval mortality showed any dose-dependent effects. Our results suggest that the early life stages of capelin are more robust to crude oil exposure than similar life stages of other fish species. The capelins demersal eggs properties, primarily the double-layered chorion was hypothesized to be a possible explanation for this trend. To verify this hypothesis, further investigation of accumulated levels in embryos and how eggs morphology affects accumulation could be investigated.